KINERJA KARYAWAN DIPENGARUHI OLEH PROGRAM PELATIHAN KARYAWAN DAN KOMPENSASI MELALUI KEPUASAN KERJA - Rohman, Rohman; Prasetyo, Indra; Hartati, Sri (STIE PENA, 2023)
The purpose of this research is to describe the program, job satisfaction, and employee performance at the Hidayatul Tholibin Baureno Bojonegoro Foundation. To analyze the influence of training programs, understanding of employee job satisfaction. To analyze the effect of training programs, understanding and job satisfaction on employee performance. To analyze the effect of training programs and damage to employee performance. This type of research is explanatory with a quantitative approach. The population of all employees of the Hidayatul Tholibin Baureno Bojonegoro Foundation is 32 people. The sample is 32 people with total sampling technique. Data analysis technique uses Partial Least Square (PLS). The results of the study state that training and compensation programs have a significant effect on job satisfaction. Training has no effect on employee performance. Compensation and job satisfaction have a significant effect on employee performance. Training and compensation programs have a significant effect on employee performance through satisfaction.Keywords: Training Program, Job Satisfaction Compensation, and Performance